Cultivo de concha prieta anadara tuberculosa a diferentes densidades en estanques camaroneros utilizando canastas de cultivo - Samaniego Cobeña, Eduardo Tairon (2008)
In the place the island "houses", belonging to the canton Santa Rosa parish Jambeli, county of the Gold, an analysis of determination of density of appropriate siembra was made for the blackish shell (tuberculous anadara), in submerged baskets of the pond camaronero in different siembra densities during 6 months of cultivation. The objectives proposed for this investigation were: 1 to determine the good density of growth of the blackish shell (tuberculous anadara). 2 to analyze the increment of weight and it carves of the shell (A.tuberculosa). The present investigation was carried out to look for new work alternatives, because the production camaronera has gone taking land to the ecosystem, which has achieved the extinction of the species, for this reason the cultivation of the mollusk blackish shell (TO Tuberculous), it focuses cultivation strategies getting the attention of the same one, and this way to improve the use of this natural resource. The cages stop the investigation they consisted on three baskets, with an area of a squared meter each a, in such a way that you/they were submerged respectively to the pond camaronero to a depth of a meter. One worked with three different densities for square meter in the three treatments these they were, 10, 15, 20 organisms with three repetitions each one. Their weight and sizes iníciales fluctuated between 25.5mm and 37,5mm in longitude and a total weight that fluctuated among 8.5g. and 14.5g. The investigation baskets were monitoreadas and cleaned every thirty days, to avoid that the baskets fill with silt which impedes the free plankton flow and organic detritus that it is good for the feeding of these organisms inside the pond camaronero. It was also considered the environmental parameters that were taken in each muestreó, giving as a result on the average during the six months of investigation, an ambient temperature of 25,61, salinidad32, 49 ‰, I oxygenate disuelto3, 56, and a pH of 7,46. Also, he/she was carried out a qualitative analysis of the organisms planctónicos found in the pond camaronero in which a variety algae fitoplanctonicas was observed among which were observed. Coscinodiscus oculus iridis, Oscillatoria, Nitzchia closterium, Nitzchia seriata, Skeletonema costatum, Rhizosolenia alata, Gyrosigma hippocampus. The results of the increment of weight average were of 4.15g. and it carves 5.40mm during the finalization of the investigation.